2020
DOI: 10.1093/humupd/dmaa022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of paternal exposure to immunosuppressive drugs on sexual function, reproductive hormones, fertility, pregnancy and offspring outcomes: a systematic review

Abstract: BACKGROUND Information regarding the possible influence of immunosuppressive drugs on male sexual function and reproductive outcomes is scarce. Men diagnosed with immune-mediated diseases and a wish to become a father represent an important neglected population since they lack vital information to make balanced decisions about their treatment. OBJECTIVE AND RATIONALE The aim of this research was to systematically review the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
19

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 163 publications
(181 reference statements)
2
33
1
19
Order By: Relevance
“…This is even more striking if we consider that several frequently prescribed anti-rheumatic drugs have been associated with reversible or irreversible testicular toxicity. 7 The majority of people aspire to have children and it is known that men desire parenthood as much as women do. [8][9][10] Nonetheless, the impact of IA on one of the most important markers of fertility, the male fertility rate (total number of children per man), [11][12][13] has never been studied before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is even more striking if we consider that several frequently prescribed anti-rheumatic drugs have been associated with reversible or irreversible testicular toxicity. 7 The majority of people aspire to have children and it is known that men desire parenthood as much as women do. [8][9][10] Nonetheless, the impact of IA on one of the most important markers of fertility, the male fertility rate (total number of children per man), [11][12][13] has never been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…This is even more striking if we consider that several frequently prescribed anti-rheumatic drugs have been associated with reversible or irreversible testicular toxicity. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Women treated with mycophenolate mofetil, methotrexate or cyclophosphamide should be advised to discontinue therapy 6 weeks, 3 months and one ovulation cycle before conception, respectively ( Patsatsi et al, 2019 ). The authors of a very recent systematic review on the effect of paternal exposure to immunosuppressive drugs on fertility, pregnancy and offspring outcomes concluded that data regarding pregnancy and offspring outcomes were limited but no significant negative effects associated with paternal immunosuppressant exposure were reported ( Perez-Garcia et al, 2020 ).…”
Section: Treatment Of Pemphigus During Pregnancymentioning
confidence: 99%
“…As revealed from existing studies, the use of NSAIDs adversely affects cardiovascular, gastric, and renal function. [ 17 , 19 ] Moreover, NSAIDs also inhibit sperm formation, interfere with sperm motility, and induce sexual dysfunction. [ 17 ] The use of biological agents also elevates the risk of infection (eg, hepatitis B and tuberculosis), and biologics are expensive and not affordable for the general population.…”
Section: Introductionmentioning
confidence: 99%